Integrating traditional ecological knowledge in heritage conservation practices: a study of indigenous cultural landscapes at Kampung Batu 6, Tapah, Perak - Nor Fauzi, Nur Raudhatul Athirah; Ahmad, Suriati (2025)
This proposal is developed within a framework of incorporation of Traditional Ecological Knowledge into heritage conservation practices pertaining to indigenous peoples’ cultural landscapes such as in Kampung Batu 6, Tapah, Perak. Traditional Ecological Knowledge is, thus, an asset built over the years for the sustainable management of land and biodiversity that resonates with the people’s way of life which in this case are the indigenous Orang Asli. This study will employ qualitative method. The methodology shall involve participant observation, semistructured interviews of 7 participants and environmental mapping to understand how Traditional Ecological Knowledge is practiced and maintained among members of the community. The time period in one week and the work supports the view that Traditional Ecological Knowledge practice is essential for safeguarding cultural heritage and biological diversity; as well as for strengthening the resilience of human-ecological landscapes. It is therefore expected that the findings from this study will draw responses on the need to incorporate Traditional Ecological Knowledge within legal frameworks to promote both biological and cultural heritage of Malaysia.